(3EOGQI GdESJKeGQ (B/s - (3YWG Gddg, eGLO CMeOs ((3YeGf(B: s (3OGQ CSGeI ddfTQ hGdJhRjY(B, s, 2011)
(3EOGQI h CSGdjH h JNWjW h eNGWQ GdGSJKeGQ, GdGSJKeGQ GdCLfHj, GdeMGaX GdGSJKeGQjI, GdCShdb GdeGdjI, GdGSJKeGQ aj GdYedjGJ GdeUQajI h GdfbOjI, GdGSJKeGQ aj GdHhQUGJ h fXGe GdahQcSs
(3HHdjhZQGajG(B: (3U(B.231-232s
Keywords: (3GdESJKeGQs; (3GdESJKeGQ `` EOGQIs